UNETHICAL BEHAVIOUR AND ITS IMPACT ON WORK PERFORMANCE AMONGST PUBLIC EMPLOYEES IN THE EDUCATION DEPARTMENT - Kuldip Singh; Arenawati Sehat Binti Haji Omar; Zalina Binti Mohd Desa (International Journal of Accounting, Finance and Business, 2021)
Ethical behaviour if not practiced has the ability of reducing employee work performance. The unethical behaviours observable that may affect employee performance include personal use, passing blame, bribery and falsification. An organization's ability to bring forth ethical behaviour that goes above and beyond the call of duty can be a key asset and one that is difficult for competitors to imitate. This article aims to advance our understanding of and confidence in the relationship between unethical behaviour and work performance by testing the degree to which unethical behaviour effects work performance of government employees. Using data collected through a survey from 133 employees working in the State Education Department we find that a negative relationship exists between unethical behaviour and work performance and that that personal use and passing blame negatively impact work performance. The data obtained through questionnaires was analyzed and evaluated by statistical test correlation to test the various hypotheses. This study provides insights on the relationship between unethical behavior and work performance in the public sector. The findings of this study may help the public sector to better understand ethical behavior work life balance and its effect on work performance. This study has some limitations and recommendations are also discussed.